Assessing Public Financing for Nutrition in Nepal (2011-2017) - World Bank (World Bank, Washington, DC, 2021)
Nepal reports better nutrition indicators than the South Asian average, though significant geographic and income-related inequalities remain in relation to nutrition outcomes. During the last decade, the government of Nepal has made proactive efforts to develop nutrition policy as a multisectoral priority. The total nutrition-related public spending in Nepal stood at 0.73 percent of gross domestic product (GDP) in FY 2016-17, up from 0.57 percent of GDP in FY 2011-12. Nutrition-related expenditure is primarily driven by nutrition-sensitive interventions, which may not directly target malnutrition but do contribute to improving general nutritional status in synergy with nutrition-specific policies. On average between FY 2011-12 and FY 2017-18, 80 percent of nutrition-related allocations were spent, and spending of allocations was higher for nutrition-sensitive interventions than for nutrition-specific interventions. The country’s new federal structure and fiscal resource allocation can be an opportunity to improve nutrition-related financing, especially nutrition-specific financing, and reduce nutritional inequalities according to regional needs.